Attenuated cardiac function degradation in ex vivo pig hearts. Issue 3 (March 2020) - Kappler, Benjamin; van Tuijl, Sjoerd; Ergin, Bülent; Fixsen, Louis; Stijnen, Marco; Ince, Can; de Mol, Bas AJM
Isolated hearts offer the opportunity to evaluate heart function, treatments, and diagnostic tools without in vivo factor interference. However, the early loss of cardiac function and edema occur over time and do limit the duration of the experiment. This research focuses on delaying these limitations using optimal blood control. This study examines whether blood conditioning by means of the combination of blood predilution and hemodialysis can significantly reduce cardiac function degradation. Slaughterhouse porcine hearts were revived in the PhysioHeart™ platform to restore physiological cardiac performance. Twelve hearts were divided into a control group and a dialysis group; in the latter group, hemodialysis was attached to the blood reservoir. Cardiac hemodynamics and blood parameters were recorded and evaluated. Blood conditioning significantly reduced the loss of cardiac pump function (control group vs dialysis group, −14.9 ± 6.3%/h vs −9.7 ± 2.7%/h) and loss of cardiac output (control group vs dialysis group, −11.8 ± 3.4%/h vs −5.9 ± 2.0%/h). Hemodialysis resulted in physiological and stable blood parameters, whereas in the control group ions reached pathological values, while interstitial edema still occurred. The combination of blood predilution and hemodialysis significantly attenuated ex vivo cardiac function degradation and delayed the loss of cardiac hemodynamics. We hypothesized that besides electrolyte and metabolic control, the hemodialysis-accompanied increase in hematocrit resulted in improved oxygen transport. This could have temporarily compensated the deleterious effect of an increased oxygen-diffusion distance due to edema in the dialysis group and resulted in less progression of cell decay. Clinically validated measures delaying edema might improve the effectiveness of the PhysioHeart™ platform.